Future of Logistics - Khaled Hanfy (International Business Logistics Journal)
The global trading system has been greatly affected by major macro-economic transformations that the world is still facing today (china- USA trade war, new economic trends such as cycle economy and sharing economy, new business applications such as e-commerce and blockchain technology, and fourth industrial revolution). In addition, the capacity and size of international trade had expanded along with foreign investments and advancements in technologies. These changes created multiple chances as well as obstacles that may result, in turn, in changing the entire worldwide trading roadmap.